Small acts of resistance: Can these lead to a positive change? - Issa, Theodora; Pick, David (European Business Ethics Network UK (EBEN), 2011)
The aim of this paper is to examine whether and how business ethics scholars can be engaged with students in critical public debate about business ethics issues. The question of whether small acts of resistance by business ethics scholars can enhance pedagogy and public engagement will be explored using data from a variety of sources including student course evaluations and reflective learning journals by students and reflections on teaching by lecturers. The paper will conclude with a discussion of issues and questions, limits and possibilities arising from the research that are worthy of further examination, particularly in relation to the support rendered by universities to business ethics scholars to enhance their engagement in both local or global debates as they seek to make a difference in the global community they are part of.